Aniba canelilla (Kunth) Mez (Lauraceae) Essential Oil: Effects on Oxidative Stress and Vascular Permeability - Eloise K. Serrão Cardoso; Karen Kubota; Diandra Araújo Luz; Paulo Fernando S. Mendes; Pablo Luis B. Figueiredo; Rafael Rodrigues Lima; Cristiane S. Ferraz Maia; Enéas Andrade Fontes-Júnior (MDPI AG, 2022)
The present study aimed to investigate the antioxidant activity of Aniba canelilla (kunth) Mez (Lauraceae) essential oil (AcEO), exploring its potential for prevention and/or treatment of oxidative stress and associated inflammatory process. With this aim, Wistar rats (n = 6/group) were pre-treated intraperitoneally with saline (0.9%) or AcEO (2 or 5 mg/kg) for 5 days. One hour after the last dose, inflammation and oxidative stress were induced by carrageenan (0.3 mg/kg; ip.) administration. Total antioxidant capacity, reduced glutathione (GSH) and lipid peroxidation levels, protein concentration, and leukocyte migration were evaluated in peritoneal fluid. Lipid peroxidation was also evaluated in plasma. Carrageenan strongly reduced the peritoneal antioxidant capacity and GSH concentration, increasing peritoneal and plasma lipid peroxidation. It also promoted increased plasma leakage and leukocyte migration. Treatment with AcEO (2 and 5 mg/kg), whose major constituent was 1-nitro-2-phenylethane (77.5%), increased the peritoneal antioxidant capacity and GSH concentrations, and reduced lipid peroxidation, both peritoneal and plasma, thus inhibiting the carrageenan-induced oxidative imbalance. AcEO also reduced the carrageenan-induced plasma leakage and leukocyte migration. These data demonstrate the AcEO antioxidant activity and its ability to modulate plasma leakage and leukocyte migration, confirming its potential for treating diseases associated with inflammation and oxidative stress.